Identification and characterization of the nano-sized vesicles released by muscle cells - Romancino, Daniele P. (FEBS Lett, 2013)
Several cell types secrete small membranous vesicles that contain cell-specific collections of proteins, lipids, and genetic material. The function of these vesicles is to allow cell-to-cell signaling and the horizontal transfer of their cargo molecules. Here, we demonstrate that muscle cells secrete nano-sized vesicles and that their release increases during muscle differentiation. Analysis of these nanovesicles allowed us to characterize them as exosome-like particles and to define the potential role of the multifunctional protein Alix in their biogenesis.